Long-term monitoring of an earth-masonry shell house in Johannesburg, South Africa: thermal performance. Issue 1 (17th February 2021) - Bradley, Ryan A.; Gohnert, Mitchell; Fitchett, Anne
Abstract : Earth has been used as a building material for millennia, and several structures built in antiquity still exist today. Recently, there has been renewed interest in earth-block masonry as it offers some benefits over more traditional materials, including sustainability, low embodied carbon dioxide and energy, good thermal performance and affordability. Additional benefits may be achieved by utilising shells for roof or structure. Of particular focus in this paper is a shell house built in Johannesburg, South Africa. It is a double-storey house, comprising interlocking masonry walls, earth-block vaults and a rib and block slab. This paper presents some in situ experimental results from a long-term thermal evaluation of the prototype house. The effectiveness of several passive design strategies was also examined. Natural ventilation and painting external surfaces white were especially effective at reducing late afternoon and evening temperatures during summer. Another important finding was that the shading of the shell's surface resulted in a significant reduction of indoor temperatures during the winter months. Specifically, the temperature within the north vault was regularly 3–5°C warmer than in the partially shaded south vault between 5.00 p.m. and 9.00 p.m. Several performance recommendations are presented for unreinforced earth-masonry shells.